SIKAP MORAL DALAM MENANTIKAN KEDATANGAN TUHAN - Hantrini Patoo (FILADELFIA: Jurnal Teologi dan Pendidikan Kristen, 2023)
This article examines theologically the morals attitude in waiting for God’s coming at the and of time or what is called the parousia teaching, nomely the second presence of Jesus Christ. In the Old Testament it is known as the day of the Lord or what is referred to as the awaited coming of the Son of man, while in the New Testament it is better known as the second coming of Jesus Christ, that is what is called the parousia. In His first coming i tis like the mystery known as the kingdom of God, which then ends His first coming. Likewise, with his second presence, he becomes a just king and judge for mankind, and separates people who are diligently faithful in carrying out His law from people who are full of sin, from this writing, i tis hoped that Christians as a church will be able to develop or realize the right way of thinking and moral behavior in waiting for the Lord’s coming.The diversity of morals attitudes can be a problem so that it can pose various challenges and apportunuties for Christian ethics, especially those related to the spirituality of the people God. Moral diversity that aften accurs raises issues that are contrary to the teachings of falth as Christians, also in terms of interpretation of the bible and the process of understanding the will of God’s plan, in responding to issue like this, this paper provides conclusions that are theological reflections about how a person can understand the teachings of faith regarding the proper morals attitude before God, so that it may become the basis and guide to being accountable when the day of God arrives. That is why is abliged to understand God’s will, so that he can apply it whenever and whenever he is, Romans 12:22 . so having morals such as love, exemplalry power, living as children of light, faith and reason etc, play a very importand role in Christian ethics in arder to prepare ourseives to weicome God’s coming in the last days.